(untitled) (Revista Electrónica de Didáctica en Educación Superior, 2015)
Se caracterizaron las percepciones que poseen los estudiantes de los Planes de Estudio 1995 y 2004 de la carrera Profesorado en Ciencias Biológicas, Universidad Nacional de Salta (U.N.Sa), acerca de los modos en que son evaluados en las diferentes asignaturas. Asimismo, se identificaron sus demandas en cuanto a estrategias tendientes a mejorar la evaluación. Se encuestaron treinta y tres (33) estudiantes mediante un cuestionario. Los resultados mostraron diferencias entre las opiniones de los alumnos de ambos planes de estudio en relación con los aspectos considerados. Palabras clave: evaluación de aprendizajes ; percepciones; demandas; profesorado; estudiantes A Comparative Study of the Students’ Perceptions and Demands on Learning Assessment in Different Curricula in the Teachers Training Degree in Biology The aim of this paper is to characterize the students’ perceptions about the evaluation process in the different subjects in the 1995 and 2004 Curricula in the Teacher Training Degree in Biology, National University of Salta (U.N.Sa.). In addition, their demands related to the strategies used for the improvement of the evaluation process were identified. Thirty-three (33) students were surveyed with questions. The results showed that the students in the two curricula have different opinions as regards the aspects under consideration. Keywords: key words; learning assessment; perceptions; demands; teacher training; students